PENGARUH MEDIA PEMBELAJARAN JAM TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA KELAS II SD NEGERI 58 BENGKULU SELATAN - Lici Inda Anggraini; Edi Ansyah; Zubaidah Bayan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the significant effect of using clock-based instructional media on the mathematics learning outcomes of second-grade. The background of this research is based on the low mathematics learning outcomes, the limited use of clock-based instructional media, the lack of teacher creativity in utilizing media according to students' needs, and the limited student interaction and engagement in learning activities.This research uses a quantitative approach with a quasi- experimental method and a pretest-posttest control group design. The sample consisted of two classes, each with 19 students, namely class II A as the experimental group and class II B as the control group. The instrument used was a multiple-choice learning outcome test.The results showed that the average pretest score of the experimental group was 31.5, which increased to 71.5 in the posttest. Meanwhile, the control group’s score increased from 27.3 to 43.6. The independent sample t-test showed a significance value of 0.011 < 0.05 and a t-count of 2.682 > t-table value of 2.028, indicating a significant difference between the two groups, indicating a significant effect after the treatment. Thus, the use of clock-based instructional media is proven to be significant and highly effective in improving the mathematics learning outcomes of second-grade elementary students.